2016
DOI: 10.18632/oncotarget.13556
|View full text |Cite
|
Sign up to set email alerts
|

Investigating cytokinesis failure as a strategy in cancer therapy

Abstract: Effective therapeutics exploit common characteristics shared amongst cancers. As many cancers present chromosomal instability (CIN), one possible approach to treat these cancers could be to increase their CIN above a threshold that would affect their viability. Here, we investigated whether causing polyploidy by cytokinesis failure could represent a useful approach. We show that cytokinesis failure caused by depletion of Citron kinase (CIT-K) dramatically decreased cell proliferation in breast, cervical and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 55 publications
3
38
0
Order By: Relevance
“…In addition, Rho-associated protein kinase serves an essential role in the metastasis and proliferation of breast cancer and hepatocellular carcinoma (31,32). The knockdown of CIT directly inhibits the proliferation of breast cancer and hepatocellular carcinoma cells (33,34). Since a previous study determined that CIT is an essential kinase that targets Rho-associated kinases (including ROCK and ROK) (27), it seems likely that CIT serves an important role in these cancers by interacting with Rho signaling.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Rho-associated protein kinase serves an essential role in the metastasis and proliferation of breast cancer and hepatocellular carcinoma (31,32). The knockdown of CIT directly inhibits the proliferation of breast cancer and hepatocellular carcinoma cells (33,34). Since a previous study determined that CIT is an essential kinase that targets Rho-associated kinases (including ROCK and ROK) (27), it seems likely that CIT serves an important role in these cancers by interacting with Rho signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Citron kinase (CIT-K) is a contractile ring component that acts as a major midbody organizer by interacting with several midbody components and maintaining their orderly arrangement 9,10 . As a first step towards the characterization of the midbody interactome, we used a human HeLa cell line stably expressing CIT-K tagged with GFP 11 to identify the CIT-K interactomes at different cell cycle stages -S phase, metaphase and telophase -by AP-MS ( Fig. 1a-b and Supplementary Data S1).…”
Section: Citron Kinase a Key Midbody Organizer Interacts With Many mentioning
confidence: 99%
“…Given their significant role and function, primarily in cytokinesis, in contrast to other kinases (eg, Aurora B and Plk1) that have different roles throughout mitosis, 34 we believe that small molecule inhibitors targeting CIT could be promising antiproliferative compounds in the treatment of MM. Moreover, we showed that cell lines with low TP53 expression due to mutations and deletions are particularly sensitive to CIT knockdown, which suggests a potential role for CIT inhibition in relapsed/refractory patients with biallelic TP53 inactivation.…”
Section: Discussionmentioning
confidence: 99%